Effect of Breathing Oxygen-Enriched Air on Exercise Performance in Patients With Pulmonary Hypertension Due to Heart Failure With Preserved Ejection Fraction: A Randomized, Placebo-Controlled, Crossover Trial - Müller, Julian; Lichtblau, Mona; Saxer, Stéphanie; Calendo, Luigi-Riccardo; Carta, Arcangelo F.; Schneider, Simon R.; Berlier, Charlotte; Furian, Michael; Bloch, Konrad E.; Schwarz, Esther I.; Ulrich, Silvia (Frontiers in Medicine, 2021)
Objective: To evaluate the effects of breathing oxygen-enriched air (oxygen) on exercise performance in patients with pulmonary hypertension due to heart failure with preserved ejection fraction (PH-HFpEF). Methods: 10 patients with PH-HFpEF (5 women, age 60±9 y, mPAP 37±14 mmHg, PAWP 18±2 mmHg, PVR 3±3 WU, resting SpO2 98±2 %) performed two cycle incremental exercise tests (IET) and two constant work-rate exercise test (CWRET) at 75 % maximal work-rate (Wmax), each with ambient air (FiO2 0.21) and oxygen (FiO2 0.5) in a randomized, single-blinded, cross-over design. The main outcomes were the change in Wmax (IET) and cycling time (CWRET) with oxygen versus air. Blood gases at rest and end-exercise, dyspnea by Borg CR10 score at end-exercise and continuous SpO2, minute ventilation (V’E), carbon dioxide output (V’CO2), cerebral and quadriceps muscle tissue oxygenation (CTO and QMTO) were measured. Results: With oxygen vs. air, Wmax (IET) increased from 94±36 to 99±36 Watts (W), mean difference (95 % CI) 5.4 (0.9 to 9.8) W, p=0.025 and cycling time (CWRET) from 532±203 to 680±76 seconds (sec), +148 (31.8 to 264) sec, p=0.018. At end-exercise with oxygen, Borg dyspnea score, V’E/V’CO2 were lower, whereas PaO2 and end-tidal PaCO2 were higher, other parameters were unchanged. Conclusion: Patients with PH-HFpEF not revealing resting hypoxemia, significantly improved their exercise performance whilst breathing oxygen-enriched air along with less subjective dyspnea sensation, a better blood oxygenation and an enhanced ventilatory efficiency. Future studies should investigate whether prolonged training with supplemental oxygen would increase the training effect and potentially daily activity for PH-HFpEF patients.